Heat Flux Condensation on Coconut Shell Activated Charcoal Porous Media - Djoko Hari Praswanto; Mochtar Asroni; Thomas Priyasmanu; Tutut Nani Prihatmi (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2020)
One way to keep the air humidity is by increasing the heat transfer with the porous media model. Increasing heat transfer depends on the value of the heat flux on the porous media. The heat flux value can be determined by inserting the porous media into the test section and then flow the vapor. The amount of heat absorbed is influenced by the large diameter of the porous on the media used. Therefore, this study aimed to optimize coconut shell charcoal by activating the charcoal. The purpose of activating coconut shell charcoal is to enlarge the pores so that it absorbs heat better than charcoal that has not been activated. The research method used is an experimental method and compares the results of research with previous studies. The porous media was vaporized for 60 minutes with a vapor temperature of 30 °C, while the vapor speed was varied, namely 1 m/s, 2m/s and 3 m/s. From the research results, that by using coconut shell activated charcoal, the heat flux value was higher than using coconut shell charcoal media. This is because the pore size in activated charcoal is larger and more numerous than charcoal that has not been activated so that it absorbs more heat. In addition, the greater the vapor speed, the higher the heat flux, because in the test section more vapor enters than vapor that comes out so that the porous media has a long time to absorb heat in the vapor. The heat transfer that occurs in porous media includes forced convection heat transfer because it has a value of Gr/Re2 < 1.